Implementation of Two-Axis Position-Based Impedance Control with Inverse Kinematics Solution for A 2-DOF Robotic Finger - Nasir, Khairunnisa; Liza Ahmad Shauri, Ruhizan; Mohd Salleh, Norshariza; Hanani Remeli, Nurul (International Journal of Engineering and Technology, 2018)
Position-based impedance control is a force control approach which consists of a single control law that accommodates the external force to achieve the desired dynamics of the body. A previously developed three-fingered robot hand was very rigid in its motion due to the application of position control alone. The position control scheme was inadequate for the tasks that involves the interaction of a robot end-effector with its environment which could damage fragile objects or be prone to slippage when provided with incorrect object's position. This paper introduces the application of two-axis position-based impedance control to one of the 2 degree-of-freedom (DOF) robotic finger of the robot hand. The goal of the control is to produce a mass-spring-dashpot system for the robot hand which considers the external force exerted by the object or environment onto the finger to modify the targeted position of the robot's tip-end. The position-based impedance control which was successfully performed however could not directly drive the DC-micromotors at the finger joints since it was expressed in the Cartesian position (X,Y,Z) form. Therefore, inverse kinematics was derived using geometrical approach to convert the Cartesian position (X,Y,Z) to angle position of motor which is controlled by PID. The proposed control and the developed kinematics were programmed using Matlab Simulink and tested in real-time experiments. The validation result has proven that the proposed position-based impedance control could modify the initial fingertip position according to the amount and direction of the applied external force, thus produced softness to the robotic finger.Â Â